Pengembangan Usaha UMKM Kemplang Panggang UMMI Melalui Implementasi Komunikasi Pemasaran - Helmita, Helmita; Misnawati, Desy; Desi Kusmindari, Christofora (LPkM Universitas Bakrie, 2023)
This community service aims to develop Micro, Small, and Medium Enterprises (MSMEs) Kemplang Panggang UMMI development through marketing communication in Bandar Lampung so that MSME products can be more widely known in the market through digital marketing communication using social media accounts. Based on the results of the interviews, it shows that these MSMEs have not implemented marketing communications using technology. This condition causes MSME products not yet known to a wide audience because they are still limited in marketing their products. The implementation methods carried out are training such as lectures, tutorials, questions and answers, also monitoring and evaluation. After counseling and mentoring, MSME actors understand how to develop MSMEs through the implementation of marketing communications through social media accounts that are loved by the community so that they are expected to expand the marketing of MSME products and further develop these MSMEs.